Diet and Exercise Improve Neutrophil to Lymphocyte Ratio in Overweight Adolescents - Wang, R.; Chen, P. J.; Chen, W. H. (International Journal of Sports Medicine, 2011)
Neutrophil to lymphocyte ratio and levels of pro-inflammatory cytokines were evaluated in overweight, male Chinese adolescents upon completing a 4-week diet and physical exercise intervention. 43 recruited, non-randomized adolescents (body mass index >25 kg/m2) completed the controlled study. Anthropometric and biologic parameters were measured pre- and post-intervention. After the 4-week intervention, participants exhibited a significant decrease in body mass, body mass index, percentage body fat, basal heart rate, diastolic blood pressure, and all body shape indices tested. A significant decrease in serum lipids (except high-density lipoprotein cholesterol) and insulin levels was observed post-intervention. The neutrophil to lymphocyte ratio was significantly lower post-intervention. Bivariate correlation analyses showed that decrement in Δneutrophil to lymphocyte ratio significantly correlated with decrement in Δinterleukin-6 and Δwhite blood cell count. Thus, a 4-week diet and physical exercise intervention significantly reduces the neutrophil to lymphocyte ratio in a population of overweight, male adolescents. Weight loss caused by the intervention was associated with a significant decrease of pro-inflammatory cytokine levels.
Keywords: obesity; NLR; IL-6; leukocytes